Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Certainly! Let's solve this problem step by step.
### Step 1: Understanding the Given Equation
We are given the equation:
[tex]\[ x^2 = 3^{\frac{2}{3}} + 3^{\frac{-2}{3}} - 2 \][/tex]
First, let's calculate the right-hand side:
1. [tex]\( 3^{\frac{2}{3}} \)[/tex] denotes the cube root of [tex]\(3\)[/tex] squared:
[tex]\[ 3^{\frac{2}{3}} = \left( 3^{\frac{1}{3}} \right)^2 \][/tex]
2. [tex]\( 3^{-\frac{2}{3}} \)[/tex] is the reciprocal of [tex]\(3^{\frac{2}{3}}\)[/tex]:
[tex]\[ 3^{-\frac{2}{3}} = \frac{1}{3^{\frac{2}{3}}} \][/tex]
Now let's compute the expression:
[tex]\[ 3^{\frac{2}{3}} + 3^{-\frac{2}{3}} - 2 \][/tex]
It simplifies to approximately:
[tex]\[ 0.56083367982104 \][/tex]
Thus, we have:
[tex]\[ x^2 = 0.56083367982104 \][/tex]
### Step 2: Solving for [tex]\(x\)[/tex]
Next, we solve [tex]\( x^2 = 0.56083367982104 \)[/tex]. Solving this,
[tex]\[ x = \pm \sqrt{0.56083367982104} \][/tex]
The solutions are approximately:
[tex]\[ x \approx \pm 0.748888295956774 \][/tex]
### Step 3: Verifying the Expression
We need to verify:
[tex]\[ 3 x \left( x^2 + 3 \right) \][/tex]
For both values of [tex]\(x\)[/tex], calculate the expression:
1. For [tex]\( x = 0.748888295956774 \)[/tex]:
[tex]\[ x^2 \approx 0.56083367982104 \][/tex]
[tex]\[ 3 x \left( x^2 + 3 \right) = 3 \times 0.748888295956774 \times \left( 0.56083367982104 + 3 \right) \][/tex]
[tex]\[ = 3 \times 0.748888295956774 \times 3.56083367982104 \][/tex]
[tex]\[ = 3 \times 0.748888295956774 \times 3.56083367982104 = 8 \][/tex]
2. For [tex]\( x = -0.748888295956774 \)[/tex]:
[tex]\[ x^2 \approx 0.56083367982104 \][/tex]
[tex]\[ 3 x \left( x^2 + 3 \right) = 3 \times (-0.748888295956774) \times \left( 0.56083367982104 + 3 \right) \][/tex]
[tex]\[ = 3 \times (-0.748888295956774) \times 3.56083367982104 \][/tex]
[tex]\[ = 3 \times (-0.748888295956774) \times 3.56083367982104 = -8 \][/tex]
Since [tex]\(3 x \left( x^2 + 3 \right)\)[/tex] for [tex]\(x = 0.748888295956774\)[/tex] gives 8, we have proven that:
[tex]\[ 3 x \left( x^2 + 3 \right) = 8 \][/tex]
### Step 1: Understanding the Given Equation
We are given the equation:
[tex]\[ x^2 = 3^{\frac{2}{3}} + 3^{\frac{-2}{3}} - 2 \][/tex]
First, let's calculate the right-hand side:
1. [tex]\( 3^{\frac{2}{3}} \)[/tex] denotes the cube root of [tex]\(3\)[/tex] squared:
[tex]\[ 3^{\frac{2}{3}} = \left( 3^{\frac{1}{3}} \right)^2 \][/tex]
2. [tex]\( 3^{-\frac{2}{3}} \)[/tex] is the reciprocal of [tex]\(3^{\frac{2}{3}}\)[/tex]:
[tex]\[ 3^{-\frac{2}{3}} = \frac{1}{3^{\frac{2}{3}}} \][/tex]
Now let's compute the expression:
[tex]\[ 3^{\frac{2}{3}} + 3^{-\frac{2}{3}} - 2 \][/tex]
It simplifies to approximately:
[tex]\[ 0.56083367982104 \][/tex]
Thus, we have:
[tex]\[ x^2 = 0.56083367982104 \][/tex]
### Step 2: Solving for [tex]\(x\)[/tex]
Next, we solve [tex]\( x^2 = 0.56083367982104 \)[/tex]. Solving this,
[tex]\[ x = \pm \sqrt{0.56083367982104} \][/tex]
The solutions are approximately:
[tex]\[ x \approx \pm 0.748888295956774 \][/tex]
### Step 3: Verifying the Expression
We need to verify:
[tex]\[ 3 x \left( x^2 + 3 \right) \][/tex]
For both values of [tex]\(x\)[/tex], calculate the expression:
1. For [tex]\( x = 0.748888295956774 \)[/tex]:
[tex]\[ x^2 \approx 0.56083367982104 \][/tex]
[tex]\[ 3 x \left( x^2 + 3 \right) = 3 \times 0.748888295956774 \times \left( 0.56083367982104 + 3 \right) \][/tex]
[tex]\[ = 3 \times 0.748888295956774 \times 3.56083367982104 \][/tex]
[tex]\[ = 3 \times 0.748888295956774 \times 3.56083367982104 = 8 \][/tex]
2. For [tex]\( x = -0.748888295956774 \)[/tex]:
[tex]\[ x^2 \approx 0.56083367982104 \][/tex]
[tex]\[ 3 x \left( x^2 + 3 \right) = 3 \times (-0.748888295956774) \times \left( 0.56083367982104 + 3 \right) \][/tex]
[tex]\[ = 3 \times (-0.748888295956774) \times 3.56083367982104 \][/tex]
[tex]\[ = 3 \times (-0.748888295956774) \times 3.56083367982104 = -8 \][/tex]
Since [tex]\(3 x \left( x^2 + 3 \right)\)[/tex] for [tex]\(x = 0.748888295956774\)[/tex] gives 8, we have proven that:
[tex]\[ 3 x \left( x^2 + 3 \right) = 8 \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.